The influence of ovariectomy, simvastatin and sodium alendronate on alveolar bone in rats Influência da ovariectomia, da sinvastatina e do alendronato sódico no osso alveolar em ratas - Ana Lia Anbinder; Fernanda de Almeida Prado; Marcela de Almeida Prado; Ivan Balducci; Rosilene Fernandes da Rocha (Sociedade Brasileira de Pesquisa Odontológica, 2007)
Bisphosphonates are currently used in the treatment of many diseases involving increased bone resorption such as osteoporosis. Statins have been widely used for the treatment of hypercholesterolemia and recent studies have shown that these drugs are also capable of stimulating bone formation. The purpose of this study was to evaluate the influence of an estrogen deficient state and the effects of simvastatin and sodium alendronate therapies on alveolar bone in female rats. Fifty-four rats were either ovariectomized (OVX) or sham operated. A month later, the animals began to receive a daily dose of simvastatin (SIN - 25 mg/kg), sodium alendronate (ALN - 2 mg/kg) or water (control) orally. Thirty-five days after the beginning of the treatment, the rats were sacrificed and their left hemimandibles were removed and radiographed using digital X-ray equipment. The alveolar radiographic density under the first molar was determined with gray-level scaling and the values were submitted to analysis of variance (a = 5%). Ovariectomized rats gained more weight (mean ± standard deviation: 20.06 ± 6.68%) than did the sham operated animals (12.13 ± 5.63%). Alveolar radiographic density values, expressed as gray levels, were lowest in the OVX-water group (183.49 ± 6.47), and differed significantly from those observed for the groups receiving alendronate (sham-ALN: 193.85 ± 3.81; OVX-ALN: 196.06 ± 5.11) and from those of the sham-water group (193.66 ± 4.36). Other comparisons between groups did not show significant differences. It was concluded that the ovariectomy reduced alveolar bone density and that alendronate was efficient for the treatment of this condition. Os bisfosfonatos são empregados atualmente para o tratamento de várias doenças caracterizadas pelo aumento da reabsorção óssea, como a osteoporose. As estatinas são amplamente utilizadas para redução de níveis elevados de colesterol e estudos recentes têm revelado sua ação anabólica no osso. O objetivo deste trabalho foi avaliar a influência da deficiência estrogênica e dos tratamentos com sinvastatina ou alendronato sódico no osso alveolar em ratas. Cinqüenta e quatro ratas sofreram ovariectomia (OVX) ou cirurgia simulada ("sham"). Um mês após, os animais passaram a receber diariamente, via oral, 25 mg/kg de sinvastatina (SIN), 2 mg/kg de alendronato (ALN) ou água (controle). Trinta e cinco dias depois do início do tratamento os animais foram sacrificados, as hemimandíbulas esquerdas removidas e radiografadas em aparelho de raios X digital. Foi calculada a densidade radiográfica em tons de cinza da área de osso alveolar sob o primeiro molar mandibular e os valores foram submetidos a ANOVA, ao nível de 5%. Ratas ovariectomizadas ganharam mais peso (média ± desvio-padrão: 20,06 ± 6,68%) que as demais (12,13 ± 5,63%). Os valores de densidade radiográfica, em tons de cinza, foram menores nos animais do grupo OVX-água (183,49 ± 6,47), significantemente diferentes daqueles observados nos grupos que receberam alendronato ("sham"-ALN: 193,85 ± 3,81; OVX-ALN: 196,06 ± 5,11) e no grupo "sham"-água (193,66 ± 4,36). Outras comparações entre grupos não revelaram diferenças estatísticas. Concluiu-se que a ovariectomia reduziu a densidade óssea alveolar e que o tratamento com alendronato sódico foi eficiente para o tratamento desta situação.